Gene expression in the mixotrophic prymnesiophyte, Prymnesium parvum, responds to prey availability - Liu, Zhenfeng; Jones, Adriane C.; Campbell, Victoria; Hambright, K. David; Heidelberg, Karla B.; Caron, David A. (Frontiers in Microbiology, 2015)
The mixotrophic prymnesiophyte, Prymnesium parvum, is a widely distributed alga with significant ecological importance. It produces toxins and can form ecosystem disruptive blooms that result in fish kills and changes in planktonic food web structure. However, the relationship between P. parvum and its prey on the molecular level is poorly understood. In this study, we used RNA-Seq technology to study changes in gene transcription of P. parvum in three treatments with different microbial populations available as potential prey: axenic P. parvum (no prey), bacterized P. paruvm, and axenic P. parvum with ciliates added as prey. Thousands of genes were differentially expressed among the three treatments. Most notably, transcriptome data indicated that P. parvum obtained organic carbon, including fatty acids, from both bacteria and ciliate prey for energy and cellular building blocks. The data also suggested that different prey provided P. parvum with macro- and micronutrients, namely organic nitrogen in the form of amino acids from ciliates, and iron from bacteria. However, both transcriptomic data and growth experiments indicated that P. parvum did not grow faster in the presence of prey despite the gains in nutrients, although algal abundances attained in culture were slightly greater in the presence of prey. The relationship between phototrophy, heterotrophy and growth of P. parvum is discussed.